Pain tolerance in patients presenting to primary care and physiotherapy services with upper limb disorders. Issue 5 (20th December 2006) - Ryall, Claire; Coggon, David; Peveler, Robert; Reading, Isabel; Palmer, Keith T
Abstract : Background: Arm pain is a common cause of incapacity for work and is often attributed to occupational activities, but in many cases the pathogenesis is unclear. Objective: To investigate whether arm pain in the absence of identifiable underlying pathology is associated with reduced tolerance of painful sensory stimuli. Methods: 133 incident cases of arm pain, recruited from primary care and physiotherapy services, were classified according to a validated diagnostic algorithm. Pain tolerance was measured at three sites in each arm in response to electrocutaneous stimulation. Associations with pain tolerance (the geometric mean of the six measurements at 5 Hz) were assessed by linear regression, and findings were summarised as proportional changes in pain tolerance. Results: Pain tolerance was generally lower than in an earlier community survey. Women had a lower tolerance than men. After allowance for sex, age, use of analgesics and anatomical extent of pain, there was no indication of reduced tolerance in patients with non-specific pain relative to those with specific local pathology. Conclusions: Pain tolerance may be generally reduced in patients presenting to medical services with arm pain, but those with non-specific pain do not seem to have lower tolerance than those with identifiable local pathology.